SKYRMION DAN MODEL EINSTEIN-SKYRME DALAM DIMENSI LIMA - Syahreza Fadhilla, Emir
In this research, the Skyrme model in a five-dimensional flat spacetime and its coupling effect with gravity through the Einstein-Skyrme model is studied. The exact solution of Skyrmion in flat space-time is obtained by solving the Bogomolny equations which are obtained by using the BPS Lagrangian method. Properties of the solution for the Einstein-Skyrme model are obtained via variational principle on the Skyrme model Lagrangian which is coupled to the Einstein-Hilbert Lagrangian. Analysis of the resulting differential equations is carried out on the boundaries. It is found that in the flat space-time, there is a spherical symmetric submodel which solution is compacton, that is submodel with the octic term, and an extension to the quartic term submodel in the form of non-spherical symmetric solution. Furthermore, for the Einstein-Skyrme Model, it is found that the Ricci Scalar is converge when physical condition such as convergence of speed of light and mass convergence is imposed. This quantity which mass function converge to is related to the total energy of kinetic term. Another finding is that boundary condition of the functions near horizon is directly related to the cosmological constant and the difference of potential value on both boundaries of r